Healthcare Sensor System Exploiting Instrumented Crutches for Force Measurement During Assisted Gait of Exoskeleton Users - Lancini, Matteo; Serpelloni, Mauro; Pasinetti, Simone; Guanziroli, Eleonora (IEEE sensors journal, 2016)
Powered exoskeletons can be used by the persons with complete spinal cord injury to achieve bipedal locomotion again. The training required before being able to efficiently operate these orthotics, however, is currently based on the subjective assessments of the patient performance by his therapist, without any quantitative information about the internal loads or assistance level. To solve this issue, a sensor system was developed, combining the traditional gait analysis systems, such as ground reaction force platforms and motion capture systems, with Lofstrand crutches instrumented by the authors. To each crutch three strain-gauge bridges were applied, to measure both axial and shear forces, as well as conditioning circuits with transmission modules and a triaxial accelerometer. An inverse dynamics analysis, on a simplified biomechanical model of the patient wearing the exoskeleton, is proposed by the authors as a tool to assess both the internal forces acting on shoulders, elbow, and neck of the patient, as well as the loads acting on joints. The same analysis was also used to quantify the assistance provided to the patient during walking, in terms of vertical forces applied by the therapist to the exoskeleton. The tests showed a therapist assistance contribution reported as a fraction of the subject body weight up to 40% with an average close to 0% and a standard deviation value of 14%. This paper presents the description of the measurement system, of the post-processing analysis, as well as the results of the proposed approach applied to a single Rewalk user during training.